Insulin-like Growth Factor 1 Signaling Axis Meets p53 Genome Protection Pathways - Werner, Haim; Sarfstein, Rive; LeRoith, Derek; Bruchim, Ilan (Frontiers in Oncology, 2016)
Clinical, epidemiological and experimental evidence indicate that the insulin-like growth factors (IGFs) are important mediators in the biochemical chain of events that lead from a phenotypically normal to a neoplastic cell. The IGF1 receptor (IGF1R), which mediates the biological actions of IGF1 and IGF2, exhibits potent pro-survival and anti-apoptotic activities. The IGF1R is highly expressed in most types of cancer and is regarded as a promising therapeutic target in oncology. P53 is a transcription factor with tumor suppressor activity that is usually activated in response to DNA damage and other forms of cellular stress. On the basis of its protective activities, p53 is commonly regarded as the guardian of the genome. We provide evidence that the IGF signaling axis and p53 genome protection pathways are tightly interconnected. Wild type, but not mutant, p53 suppresses IGF1R gene transcription, leading to abrogation of the IGF signaling network, with ensuing cell cycle arrest. Gain-of-function, or loss-of-function, mutations of p53 in tumor cells may disrupt its inhibitory activity, thus generating oncogenic molecules capable of transactivating the IGF1R gene. The interplay between the IGF1 and p53 pathways is also of major relevance in terms of metabolic regulation, including glucose transport and glycolysis. A better understanding of the complex physical and functional interactions between these important signaling pathways will have major basic and translational relevance.